Environmental & architectural phenomenology. Vol. 16, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2005)
Vol. 16, No. 1, Winter 2005 (includes "items of interest," “citations received,” review on Mindy Thompson Fullivolve's Root Shock, and essays by Rodney Teague & Curtis Thorpe).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals